1996
DOI: 10.1096/fasebj.10.2.8641560
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐enriched transcription factors and hepatocyte differentiation

Abstract: Liver-specific gene expression in adult hepatocytes relies on four families of evolutionary conserved transcription factors that are liver-enriched but not restricted to this tissue. These factors function in unique combinations, often synergistically, to stimulate cell-specific transcription. Each family is composed of several members displaying similar, if not identical, DNA recognition properties and sharing structural homology in their DNA binding domains. The homo- and heterodimerization between members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
380
0
17

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(405 citation statements)
references
References 50 publications
8
380
0
17
Order By: Relevance
“…The differentiation is regulated by cell type-specific gene expression, which is controlled by distinct sets of transcription factors including HNFs (Cereghini, 1996;Darlington, 1999). The present study showed that normal human hepatocytes express HNF-4␣, whereas BEC do not, suggesting that HNF-4␣ plays a crucial role in the maintenance of normal hepatocyte function.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The differentiation is regulated by cell type-specific gene expression, which is controlled by distinct sets of transcription factors including HNFs (Cereghini, 1996;Darlington, 1999). The present study showed that normal human hepatocytes express HNF-4␣, whereas BEC do not, suggesting that HNF-4␣ plays a crucial role in the maintenance of normal hepatocyte function.…”
Section: Discussionsupporting
confidence: 47%
“…Transcription factors are generally controlled at two different levels, namely concentration and activity, each of which can be modulated in a variety of ways (Cereghini, 1996;Darlington, 1999). It is interesting to note that the level of the HNF expression in residual hepatocytes was low compared with that in ductular hepatocytes or regenerative hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HNF4α regulates the expression of genes in liver, both directly and indirectly, through interaction with other HNFs, including the variant homeodomain protein HNF1α, C/EBPs (CCAAT/enhancerbinding proteins), HNF3 winged helix factors and the one-cut homeoprotein, HNF6 [4]. These HNFs are, in turn, regulated through a complex transcriptional-control hierarchy that determines the relative expression and activity of other HNF family members.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It comprises factors from several families that have been identified through biochemical and genetic studies. These include the CCAAT/enhancer binding proteins, the proline acidrich factors, the homeodomain proteins of the hepatocyte nuclear factor (HNF)-1 family, winged helix proteins (HNF-3/FoxA), nuclear receptors (HNF-4, LXR, FXR and FTF/hB1F/CPF families), and the Onecut (OC) factors (HNF-6/OC-1, OC-2 and OC-3).…”
mentioning
confidence: 99%